High photothermal conversion efficiency of RF sputtered Ti4O7 Magneli phase thin films and its linear correlation with light absorption capacity - L. Pichon; H. Rekik; H. Arab; P. Drogui; M. A. El Khakani (Scientific Reports)
Abstract RF-sputtering is used to deposit Ti4O7-Magneli-phase films onto various substrates at deposition temperatures (T s ) ranging from 25 to 650 °C. Not only the structural, but also electrical conductivity, optical absorbance and photothermal properties of the Ti4O7 films are shown to change significantly with T s . A T s of 500 °C is pointed out as the optimal temperature that yields highly-crystalized pure-Ti4O7-Magneli phase with a densely-packed morphology and a conductivity as high as 740 S/cm. The Ti4O7 films deposited at T s = 450–500 °C also exhibited the highest optical absorption over all the broad (200–1500) nm range. The absorbed sunlight (AM1.5) was efficiently converted into heat by raising the temperature of the Ti4O7 films up to ~ 54 °C. Thus, the external photothermal efficiency (ηext) of the Ti4O7 films, was found to be as high as ~ 74%. This is the highest ηext reported so far for sputtered-Ti4O7 coatings (just ~ 450 nm-thick), highlighting their significant potential for photothermal applications such as desalination, deicing and/or smart windows. Finally, the ηext of the Ti4O7 coatings is demonstrated, for the first time, to be linearly correlated to their integrated light absorption coefficient. This fundamental relationship paves the way towards the design and optimization of highly efficient solar-thermal conversion devices.